Effect of the combination of small dose analgesic and music on labor pain - S Phumdoung; A Bhitakburapa; B Chanaudom; T Ajasareyasing; T Petcharat (Journal of Health Science and Medical Research (JHSMR), 2007)
A factorial randomized control trial study was undertaken to examine the effect of the combination of small dose analgesic and music on labor pain. A random block design was used to assign participants to each of four groups: control (n = 45), small dose analgesic (n = 43), regular dose analgesic (n = 45), and music plus small dose analgesic (n = 47). Women in the control group received standard care in the labor room; women in the small dose analgesic group received intramuscular meperidine 25 mg; women in the regular dose group received intramuscular meperidine 50 mg. Women in the last group received instrumental music without lyrics combined with small dose analgesic. Women entered the study when cervical dilation was 3-4 cm and contractions lasting 40-60 seconds occurred. One-way repeated measures analysis of variance (ANOVA) indicated that there were significantly different sensations and distress of labor pain among the four groups [F(3,176) = 3.651, p < .05, power .80 and F(3,176) = 4.888, p < .01, power .90 respectively]. Pairwise comparisons showed that the regular analgesic group and the music plus small dose analgesic group had lower sensation of pain and distress of labor pain than the control group. The results suggest that the use of music together with small amounts of analgesic can decrease labor pain, similar to the use of regular doses of an analgesic drug alone. The use of either dose of the analgesic drug had no adversed effect on Apgar scores of the infants in all groups.